Can China Grow Faster? : A Diagnosis of the Fragmentation of Its Domestic Capital Market - Wei, Shang-Jin (IMF Working Papers; Working Paper ;, 2004)
This paper examines possible segmentation of the internal capital market in China. We employ two standard tools from the international finance literature to analyze financial integration across Chinese provinces. Both tests confirm a similar (and somewhat surprising) picture: capital mobility within China is low! Furthermore, the degree of internal financial integration appears to have decreased, rather than increased, in the 1990s relative to the preceding period. Finally, we document that the government tends to reallocate capital from more productive regions to less productive ones. In this sense, a smaller role of the government in the financial sector might increase the rate of economic growth.